Palaeomagnetism and age of mid-Palaeozoic ring complexes in Niger, West Africa, and tectonic implications - Hargraves, R. B.; Dawson, E. M.; Houten, F. B. (Geophysical Journal International, 1987)
Detailed AF and thermal demagnetization has been performed on 185 oriented samples from 36 sites in a series of basic to acid subvolcanic ring complexes in central and southern Niger. Published Rb—Sr whole rock and mineral isochrons from acid members of the suite range — north to south — from 480 Ma to 320 Ma. Two distinct vectors have been isolated by linear regression of demagnetization data: <l type="tab"> (1) A due north and negative inclination (rarely reversed) component is present in basic rocks from 12 sites in four distinct northern complexes (published Rb—Sr ages date from 480 Ma to 420 Ma). This component is carried by ∼single domain magnetite (occasionally also by titanhaematite) and is considered to be primary, acquired during the terminal stages of this igneous episode. 40Ar/39Ar dating of biotite from three samples used in the palaeomagnetic study yield ∼435 Myr ages. (2) A due north and positive inclination (rarely reversed) direction is present as a second component in some of the basic-suite sites and is the predominant component in most sites in syenitic to granodioritic rocks. Primary Fe—Ti oxides are rare in these acid igneous rocks, and the feldspars within them are usually pervasively altered. This component, carried primarily by haematite, is believed to be either a modern day VRM, or a secondary TCRM acquired during (hydro?) thermal activity associated with widespread Quaternary volcanism in the southern Air. (3) The primary component gives a mean south pole at 43.4S, 08.6E; ( n = 12, k = 50, α 95 = 6.2) located southwest of Cape Town. This position requires a rapid southward excursion of the Gondwana A.P.W. path in early Silurian time, but it is generally consistent with most of the other Silurian/Devonian palaeomagnetic data from Gondwana. These, however, are from the Lachlan Fold Belt in southeast Australia whose relation to the Australian craton in Early Palaeozoic time is not clear. Integrating all stratigraphic, palaeoclimatic, tectonic, and other palaeomagnetic data for ...